Mr. Wuffles! [videorecording (DVD)] - Wiesner, David; Berneis, Susie (Dreamscape Media, LLC, 2014)
Mr. Wuffles is a cat who loves to play with a little spaceship full of actual aliens-but the ship wasn't designed for this kind of rough treatment. When the space visitors dodge the cat and take shelter behind the radiator to repair the damage, they make a host of insect friends. The result? A humorous exploration of cooperation between aliens and insects, and of the universal nature of communication involving symbols, 'cave' paintings, and gestures of friendship.